Dynamic Relationship between Stakeholders’ Demands, Environmental Accounting Disclosure and Financial Performance of Manufacturing Firms in Nigeria - Ewesesan, Najeem Bamidele; Akinlo, Olayinka Olufisayo; Salawu, Rafiu Oyesola; Inneh, Eghosa Godwin; Olayiwola, John Ayobamibo; Ogundele, Omobolade Stephen; Akanni , Ganiyat Dolapo (International Review of Management and Marketing, 2026)
Despite growing stakeholder pressure and regulatory attention, manufacturing firms in Nigeria still exhibit inadequate environmental disclosure practices, raising concerns about its implications for financial performance and commitment to sustainability. Hence, the study aimed the examine the dynamic relationship between stakeholders’ demands, environmental accounting disclosure and the financial performance of manufacturing firms in Nigeria. The study explored both primary and secondary data. The study employed a longitudinal research design combining primary data from 280 stakeholders. The secondary data were obtained from the annual reports and accounts of 30 sampled firms listed on the Nigerian Exchange Group from 2008 to 2023. A Vector Autoregressive (VAR) model was applied to analyse the short- and long-term interaction among the variables. The findings revealed that environmental accounting practices are relatively autonomous but increasingly influenced by stakeholder demands over time and both factors significantly enhance financial performance. The results underscore the growing interdependence between corporate environmental accountability and stakeholder expectations, highlighting that firms prioritizing transparency and engagement experience improved financial outcomes. Based on the findings, the study recommends stricter enforcement of environmental regulations, the introduction of incentive schemes for sustainable practices, adoption of standardized reporting frameworks, active stakeholder engagement and integration of environmental accounting strategic planning. The study contributes to empirical evidence on the relevance of aligning environmental practices with stakeholder expectations to achieve sustainable business outcomes in Nigeria’s manufacturing sector.